2004
DOI: 10.1007/s00330-004-2246-z
|View full text |Cite
|
Sign up to set email alerts
|

Locally advanced breast cancer: comparison of mammography, sonography and MR imaging in evaluation of residual disease in women receiving neoadjuvant chemotherapy

Abstract: The accuracy of mammography, sonography and magnetic resonance imaging (MRI) in identifying residual disease after neoadjuvant chemotherapy is evaluated and imaging findings are correlated with pathologic findings. Fifteen patients enrolled in an experimental protocol of preoperative neoadjuvant chemotherapy underwent clinical examination, mammography, sonography and dynamic MRI, performed in this order, before and respectively after 2 and 4 cycles of neoadjuvant chemotherapy. Four radiologists, two for mammog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
132
1
11

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(148 citation statements)
references
References 26 publications
(37 reference statements)
2
132
1
11
Order By: Relevance
“…In addition to treating detectable disease before surgery, neoadjuvant chemotherapy provides the earliest chance to treat micrometastatic disease, saving time that potentially could be lost to local treatment. 18 Unlike adjuvant therapy in which considerable vascular remodeling can occur at the site of tumor excision, neoadjuvant therapy is able to use the tumor's local vasculature, potentially enhancing the local effect of chemotherapy through an undisturbed blood supply. 19,20 Neoadjuvant therapy already is the standard of care in locally advanced BC (LABC) and inflammatory BC (IBC).…”
Section: Neoadjuvant Chemotherapy For the Treatment Of Breast Cancermentioning
confidence: 99%
“…In addition to treating detectable disease before surgery, neoadjuvant chemotherapy provides the earliest chance to treat micrometastatic disease, saving time that potentially could be lost to local treatment. 18 Unlike adjuvant therapy in which considerable vascular remodeling can occur at the site of tumor excision, neoadjuvant therapy is able to use the tumor's local vasculature, potentially enhancing the local effect of chemotherapy through an undisturbed blood supply. 19,20 Neoadjuvant therapy already is the standard of care in locally advanced BC (LABC) and inflammatory BC (IBC).…”
Section: Neoadjuvant Chemotherapy For the Treatment Of Breast Cancermentioning
confidence: 99%
“…Ayrıca yanıt durumuna göre bu olgulara mastektomi yerine koruyucu tedavi de uygulanabilir. Tümörün gerçek boyutlarını MRG, tüm yöntemlerden daha üstün olarak belirleyebilmektedir [39][40][41][42][43][44][45]. Kemoterapinin indüklediği fibrozis nedeniyle klinik bakıda tümör normalden daha büyük ölçülmekte, mamografide de yoğun doku değerlendirmeye engel olmaktadır.…”
Section: Neoadjuvan Tedavi Sonrası İzlemunclassified
“…Manyetik rezonans görün-tüleme ile fibrozis ve canlı tümör ayırt edebilir, doğruluğu da meme yapısının yoğunluğundan etkilenmez. Zaman/intensite eğrisi az ve yavaş kontrastlanmanın belirteci olarak tedavide basıklaşır ve sağa kayar [39][40][41][42][43][44][45].…”
Section: Neoadjuvan Tedavi Sonrası İzlemunclassified
“…To assess clinical tumour response, physical examination, breast ultrasound, mammography, and breast magnetic resonance imaging may be used (Fiorentino et al, 2001;Denis et al, 2004;Londero et al, 2004;Yeh et al, 2005), whereas breast MRI was found to be the most accurate to evaluate tumour response to NACT (Croshaw et al, 2011;Marinovich et al, 2013). Definition and assessment of clinical complete response (cCR) differed relevantly among several imaging studies even if the procedures were based on the WHO (Miller et al, 1981) or the EORTC/ RECIST (Eisenhauer et al, 2009) definitions.…”
mentioning
confidence: 99%